Fintech-Based Banking Economics Learning to Improve Students' Understanding of the Modern Financial System - Hatidah, Hatidah (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
This research aims to analyze the effectiveness of fintech-based banking economics learning in improving students' understanding of the modern financial system. This research is grounded in the gap between conventional banking education in the classroom and the rapid development of the digital finance industry. The research method is a quantitative, one-group pretest–posttest quasi-experimental design. The research subjects were 30 students from the financial management study program. The research instruments include a test of understanding of the modern financial system, a fintech literacy questionnaire, and a learning activity observation sheet. The data analysis used paired-samples t-tests and N-gain tests, along with descriptive analysis of qualitative data. The results showed a significant increase in pretest-to-posttest scores (p < 0.05), with an average N-gain of 0.62, which was in the medium to high range. In addition, observations showed increased student involvement and a positive response to the use of fintech in learning. These findings indicate that fintech-based learning is effective in improving students' cognitive and contextual understanding. This research is expected to serve as a reference for the development of banking economics learning that is more relevant to the needs of the digital financial industry.